2016
DOI: 10.1002/mnfr.201600026
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine promotes intestinal SIgA secretion through intestinal microbiota and IL‐13

Abstract: Glutamine supplementation appears to enhance SIgA secretion in the mouse intestine through the intestinal microbiota and subsequently through T cell-dependent and T cell-independent pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 52 publications
7
75
0
Order By: Relevance
“…Compelling evidence from well-designed investigations have shown that glutamine supplementation increases the abundance of SIgA in the intestine in various hosts, including rats (4, 5), mice (6, 7), Chinese Holstein calves (8), pigs (9), humans (10), and even broiler chickens (11). Similarly, we found that glutamine supplementation increases SIgA in the luminal contents of the jejunum and ileum, and the number of IgA + plasma cells in the ileum in mice (12). However, underlying mechanisms by which glutamine promotes the production of intestinal SIgA are unknown.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Compelling evidence from well-designed investigations have shown that glutamine supplementation increases the abundance of SIgA in the intestine in various hosts, including rats (4, 5), mice (6, 7), Chinese Holstein calves (8), pigs (9), humans (10), and even broiler chickens (11). Similarly, we found that glutamine supplementation increases SIgA in the luminal contents of the jejunum and ileum, and the number of IgA + plasma cells in the ileum in mice (12). However, underlying mechanisms by which glutamine promotes the production of intestinal SIgA are unknown.…”
Section: Introductionmentioning
confidence: 69%
“…Collectively, glutamine regulation of production of intestinal SIgA may be mediated by the intestinal microbiota. Indeed, our recent study using fluorescence in situ hybridization (FISH) analysis revealed that glutamine supplementation increases intestinal microbiota invasion into the wall of the ileum (12). Interestingly, disruption of the mouse intestinal microbiota with an antibiotic cocktail (37, 38) during glutamine supplementation abrogates the influence of glutamine supplementation on secretion of SIgA (12).…”
Section: Glutamine and Generation Of Intestinal Sigamentioning
confidence: 99%
See 2 more Smart Citations
“…The possible reason for nutrient-induced change of intestinal microbiota is that nutrient alters the microenvironment for intestinal microbiota, such as composition and metabolism of intestinal microbiota, and immune responses of host. Glutamine supplementation promotes mouse intestinal secretory IgA (SIgA) production and IgA + plasma cell numbers through T cell-dependent (e.g., IL-5, IL-6, and IL-13) and T cell-independent pathways [e.g., transforming growth factor (TGF- β ), a proliferation-inducing ligand (APRIL), and B cell-activating factor (BAFF)] of SIgA induction, which are largely dependent on glutamine's effect on intestinal microbiota [30]. Dietary chitosan supplementation significantly shapes the intestinal microbiota in mouse model [31].…”
Section: Diet and Oamentioning
confidence: 99%